Keputusan Vladimir Putin dalam Kebijakan Special Military Operation (SMO) Terhadap Ukraina Pada Tahun 2022 - Richard Ivander Arli; Haiyyu Darman Moenir; Rifki Dermawan (Andalas Institute of International Studies, 2022)
Russia launched a Special Military Operation (SMO) against Ukraine on February 24, 2022. The operation was based on Volodymyr Zelensky's planned membership of Ukraine to NATO in 2021. Vladimir Putin perceived the plan as a threat to Russia's core strategic interest in its national security. This decision has in fact put Russia on various international sanctions and condemnation. This study aims to explain the policy-making process that Vladimir Putin went through as president of Russia in that policy. The process will be analyzed using polyheuristic theory, which in its analysis is divided into two stages, namely the cognitive stage and the rational choice stage. This research is categorized as qualitative research with a descriptive analysis approach, utilizing secondary data. At the cognitive stage, there were three alternative options Putin had: the imposition of economic sanctions, continuing negotiations with the US, NATO, and Ukraine, and launching the military operation. Putin then decided to launch the military operation because it was considered rational to the interests of his domestic political dimension. This is aligned with the lexicographic decision rule identified at the rational choice stage, that Putin in deciding the SMO tends to ignore profits on other dimensions, such as the economy. Putin's preferred advantage corresponds to the support of the public and Russian elites, which is obtained by strengthening Russia's negotiating position against the United States, Ukraine, and NATO, and Russia's position as a great power.